(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
This study discusses the phenomenon of money laundering and its impact on the financial sector in general and the Iraqi banking sector. The research methodology describes money laundering in detail and the three basic stages of money laundering, placement, layering, and integration. How and where money laundering is a key reason to address this problem and what is the role of governments? It also deals with the impact of money laundering on the Iraqi economy, which is the theft of banks, the suspension of industrial projects, terrorism and corruption. The most important recommendations that limit this phenomenon is international cooperation and legal assistance in money laundering investigations. The use of programming and electronic systems to enter the information of owners of real estate and businesses to detect suspicious activities. To reduce this problem requires the establishment of specialized units in the Central Bank and the Ministry of Finance, Justice and the security services to apply all laws against money laundering. As for the Iraqi banking sector, it is necessary to verify the identity of the owners of the funds deposited in banks. Inform the competent authorities by the bank’s management of any suspicious activity. In addition to confirming the documents proving the legality of the funds deposited.